Dari keluhan menuju perbaikan: Pelayanan customer pembuatan buku pelaut di KSOP kelas II Kendari - Andi Rachmianty; Arif Fuddin Usman; Andi Ulfiatun; Muslihati (Departemen Teknik Kelautan Universitas Hasanuddin, 2026)
Maritime public services play a crucial role in supporting seafarers’ mobility and ensuring navigational safety. However, technical and procedural challenges often affect service quality, particularly in the issuance of seamen’s books at the Port Authority and Harbor Master Office (KSOP) Class II Kendari. This study aims to evaluate the performance of seamen’s book services and propose strategies for service improvement. A quantitative descriptive approach was employed, with data collected from 64 respondents using a questionnaire based on the SERVQUAL dimensions. The data were analyzed using the Customer Satisfaction Index (CSI) to measure satisfaction levels and Fishbone Analysis to identify root causes of service problems. The findings revealed a CSI score of 86.22%, categorized as “very satisfied,” with the highest performance attributed to staff competence. Nonetheless, several service gaps were identified, including unstable digital infrastructure, a lack of information boards, limited user awareness, and inconsistent staff responsiveness. These results suggest that enhancing digital infrastructure, improving information dissemination, and providing regular staff training are crucial to achieving optimal service quality. In conclusion, the performance of KSOP Class II Kendari has generally met user expectations but requires targeted improvements to strengthen service efficiency and user satisfaction.